The conservation values of Yakutian Cattle - Ovaska, Ulla; Soini, Katriina (Cambridge Journals, 2011)
The loss of biodiversity has become a major environmental issue during the course of the twentieth century. Numerous indigenous farm animal breeds have been replaced by commercial breeds in agricultural production processes in industrialized countries, sometimes resulting in complete breed loss and at other times placing the breed in an endangered status. Loss of breeds occurs mainly due to the striving for more intensive production, which often means that indigenous farm animal breeds are kept in conventional production only in marginal agricultural areas. One such endangered breed is the Yakutian Cattle, an indigenous Siberian cattle breed that is kept in the Russian Far East. The cattle have a low output but valuable characteristics that confer adaptation to the northern environment. This article addresses the socio-cultural and political context of conservation of the cattle at different levels in society. The conservation of animal genetic resources is embedded in the international agenda, and the Russian Federation has ratified conventions to protect them. The conservation is de facto organized at the republic level. The local communities carry out the conservation in practice by keeping and maintaining the cattle, although the conservation was initiated by the scientific community. We suggest that the conservation of Yakutian Cattle is based on national and local interests, rather than on global conventions on biological or cultural diversity. Furthermore, the reasons for conservation are different at different levels, which constitute both an advantage and a challenge for the future.
Keywords: Ma; Jakutian karja; geenivarat; genetic resources conservation; biodiversity conservation; Yakutian cattle